2004
DOI: 10.1097/01.asn.0000143475.39388.de
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Center Differences in Hemodialysis Adequacy in Children Treated at Pediatric Centers

Abstract: Abstract. This study assessed hemodialysis adequacy in pediatric centers. Monthly adequacy data were requested in NAPRTCS enrollees on hemodialysis for at least 6 mo. Data forms were returned for 147 children from 32 centers. Data are presented for the 138 children (57% boys, 45% black) that were dialyzed 3 times/wk, representing 2282 patientmonths of follow-up. Pre-and postdialysis BUN levels were reported in all children. Kt/V values were reported in 76 children; however, sufficient data were obtained to cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
2
10
1
Order By: Relevance
“…Similar to findings by Leonard et al, African American children were found to have less adequate dialysis than white children (23). Despite the presence of these differences, stratification demonstrates that disparities in survival persist in African American patients with appropriate spKt/V values.…”
Section: Discussionsupporting
confidence: 84%
“…Similar to findings by Leonard et al, African American children were found to have less adequate dialysis than white children (23). Despite the presence of these differences, stratification demonstrates that disparities in survival persist in African American patients with appropriate spKt/V values.…”
Section: Discussionsupporting
confidence: 84%
“…No difference was observed, despite the White patients in this cohort being smaller (as indicated by height and weight SDS) than the Black patients, which might be expected to result in higher estimations of clearance among White peritoneal dialysis patients. This finding is in contrast to that in studies of pediatric hemodialysis patients, where Black patients have been shown to be more likely to receive a dialysis dose below the recommended KDOQI minimum than Whites [16].…”
Section: Discussioncontrasting
confidence: 55%
“…In this pediatric population, adequate access creation is difficult and is complicated by the additional responsibility to preserve future access sites in children who may require chronic hemodialysis [2]. The types of access used in children, in decreasing order of popularity, include catheters, arteriovenous fistulae, and arteriovenous grafts [1]. The Vascular Access group publishes clinical practice guidelines and recommendations on hemodialysis access placement.…”
mentioning
confidence: 99%
“…Pediatric patients requiring hemodialysis comprise less than 1% of the total population on hemodialysis in the United States [1]. In this pediatric population, adequate access creation is difficult and is complicated by the additional responsibility to preserve future access sites in children who may require chronic hemodialysis [2].…”
mentioning
confidence: 99%